Study on complications and their associated factors of total thyroidectomy for management of benign thyroid disease in kelantan - Karim, Khasnizal Abd (2007)
Objectives: To study on safety of total thyroidectomy as a management of benign thyroid disease done at Hospital Universiti Sains Malaysia (HUSM) and Hospital Kota Bharu (HKB) and the prevalence of occult malignancy in benign thyroid disease. Methodology: A retrospective study using previous record of patients with benign thyroid disease who underwent total thyroidectomy, admitted to Hospital Universiti Sains Malaysia (HUSM) and Hospital Kota Bharu (HKB) from 1st January 2000 until 31st December 2005 ( 6 years duration).Results: 156 patients involved in this study with 143 (91.7%) female and 13 (8.3%) male with mean age 42.36 ± 13.58 years. Majority 136 (87.2%) were Malays. 98 (62.8%) had multinodular goiter, 38 (24.4%) and 20 (12.8%) had diffuse and solitary goiter respectively. FNAC showed 67 (42.9%) and 66 (42.3%) had multinodular goiter and colloid goiter respectively. 138 (88.5%) were euthyroid whereas 17 (10.9%) had thyrotoxicosis and 1 (0.6%) had hypothyroidism. No mortality was reported in my study. Postoperative bleeding occurred in 8 (5.1 %) whereas 3 (1.9%) had postoperative surgical site infection. 27 (17 .8%) and 10 (6.6%) of patients had transient and permanent recurrent laryngeal nerve palsy respectively whilst 38 (24.7%) had transient hypocalcaemia and 27 (17.5%) had permanent hypocalcaemia. Shortness ofbreath (p value= 0.022) and preoperative hoarseness of voice (p value = 0.038) were significantly associated factors for RLN injury whereas preoperative diagnosis of multinodular goiter (p value = 0.006) was significantly associated factor for post-operative hypocalcaemia. The prevalence of frank malignancy from HPE report was 13 (8.3%) whereas that of occult malignancy was 11 (7.1 %). Conclusion: Higher rates of recurrent laryngeal nerve palsy and hypocalcaemia contributed by the facts that the total thyroidectomies were done at non-specialized hospital by general surgeons or surgical trainees with supervision.